Peningkatan Kinerja Melalui Insentif Pegawai Pada Balai Pelatihan Tenaga Kerja Dan Transmigrasi (BPTT) Jambi - Reni Devita; Muhammad Emil (Universitas Batanghari Jambi, 2021)
Incentives at training of Balai Pelatihan Tenaga Kerja dan Transmigrasi (BPTT) Jambi in the past five years is growth. The average total absenteeism without explanation in the past five years as much as 17,80 %. Average of performance growth amounted to 10,64%. Indicators of incentives that cooperation, identity, competence, as well as various forms of engagement system allowances, indicators of motivation is, engagement, commitment, satisfaction and turn over, and indicator of perfomanceis quality, quantity, timeliness, cost effectiveness, the need for supervision, and interpersonal impact. Analyst tools with multiple linear regression. Balai Pelatihan Tenaga Kerja dan Transmigrasi (BPTT) Jambi is one of the technical implementation elements which organizes and is directly responsible to the Head of the Social Service Office of Manpower and Transmigration in Jambi Province. Balai Pelatihan Tenaga Kerja dan Transmigrasi (BPTT) Jambi Carry out skills training for job seekers and training in increasing labor productivity in all business sectors in government agencies, BUMN, BUMD, and Cooperatives, as well as conducting training for transmigrants and / or prospective transmigrants. Based on the table above, it is known that the value of the correlation coefficient (R) is 0.585, then the correlation between Performance (Y) through the Incentive variable (X) is 0.585, this means a close relationship because the value is close to 1. SPSS 20 result obtained equation Y= 1,014 + 0,567. From the equation it can be said that incentives variabels can be used as a tool to predict the performance of employees at Balai Pelatihan Tenaga Kerja dan Transmigrasi (BPTT) Jambi. Based on the value of the coefficient of determination r2 is 0.342, it means that there is a fairly close positive relationship between the variable Performance Improvement (Y) which influences through the Incentive variable (X). This figure states that the incentive variable (X) is able to explain the Performance variable (Y) at Balai Pelatihan Tenaga Kerja dan Transmigrasi (BPTT) Jambi by 34.2% while 65.8% is influenced by other variables outside the modeling. It is suspected that the increase in employee performance through incentives at the Balai Pelatihan Tenaga Kerja dan Transmigrasi (BPTT) Jambi with the following discussion:The effect of incentive on employee performance evidenced from tcount> ttable (4.141 > 2.034) and a significance value of < 0.05 (0.000 < 0.05) Thus, H0 is rejected, so the incentives partially affect the performance improvement. The value of tcount is positive, meaning that if the incentives increase, the performance will also increase.